2018
DOI: 10.1111/cogs.12687
|View full text |Cite
|
Sign up to set email alerts
|

Event Structures Drive Semantic Structural Priming, Not Thematic Roles: Evidence From Idioms and Light Verbs

Abstract: What are the semantic representations that underlie language production? We use structural priming to distinguish between two competing theories. Thematic roles define semantic structure in terms of atomic units that specify event participants and are ordered with respect to each other through a hierarchy of roles. Event structures instead instantiate semantic structure as embedded sub‐predicates that impose an order on verbal arguments based on their relative positioning in these embeddings. Across two experi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 78 publications
1
19
0
Order By: Relevance
“…Bock [ 9 ] first discovered structural priming in an experimental setting: In a series of tasks disguised as a recognition memory test, speakers were more likely to choose a passive structure (e.g., The church is being struck by lightning ) over an active structure (e.g., The lightning is striking the church ) to describe a picture after they heard a passive sentence. Structural priming is often considered as an effect that entails the autonomous repetition of syntactic structures independent of processing at other linguistic levels such as lexical access ([ 9 , 15 , 16 ], but see [ 17 ]). Nevertheless, it was also found that lexical overlap considerably enhances the magnitude of structural priming (i.e., lexical boost).…”
Section: Introductionmentioning
confidence: 99%
“…Bock [ 9 ] first discovered structural priming in an experimental setting: In a series of tasks disguised as a recognition memory test, speakers were more likely to choose a passive structure (e.g., The church is being struck by lightning ) over an active structure (e.g., The lightning is striking the church ) to describe a picture after they heard a passive sentence. Structural priming is often considered as an effect that entails the autonomous repetition of syntactic structures independent of processing at other linguistic levels such as lexical access ([ 9 , 15 , 16 ], but see [ 17 ]). Nevertheless, it was also found that lexical overlap considerably enhances the magnitude of structural priming (i.e., lexical boost).…”
Section: Introductionmentioning
confidence: 99%
“…Event representations from this perspective are representations of the meanings of certain types of sentence—namely, sentences that are aspectually “events” (Vendler, 1967). Linguistic argumentation and psycholinguistic experiments provide some very subtle ways of studying the semantic representations of sentences, and so offer an alternative, highly informative, empirical window onto event representations (see e.g., Levin, 2015; Ziegler, Snedeker, & Wittenberg, 2018). It is parsimonious to posit that the event representations constructed during perceptual processing, that mediate access to LTM, are the same as those studied by linguists that encode the meaning of sentences reporting events.…”
Section: Introductionmentioning
confidence: 99%
“…Another final point to note is that many studies of structural priming have focused on the effect of distance, or lag, between prime and target sentences, particularly in the debate between models of structural priming (i.e., the implicit learning account, Chang et al, 2006 and the residual activation account, Pickering and Branigan, 1998). Though the materials of the current study included prime-target pairs separated by 0, 1, or 2 filler sentences, the task was not explicitly designed to test this lag effect.…”
Section: Discussionmentioning
confidence: 99%